PENGARUH TAYANGAN TELEVISI TERHADAP PERKEMBANGAN KOGNITIF PADA ANAK USIA DINI - Rahmadia, Suci; Rahmayanty, Dinny; Nurhayati, Nurhayati; Kurniati, Wilujeng; Permata Sari, Indah (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2024)
Early childhood, which ranges from 0-6 years of age, is a period of growth and development that is very important for the child's future. This is also known as the golden age or golden age. This period is also very important to determine the next stage of growth and development of the child. In this era of highly advanced globalization, there are many emerging technologies that can have an impact on everyone, including early childhood, in this case toddlers, one of which is television. The method used in writing this article is a literature review, namely a literature search, both international and national. References are obtained through publish or perish. Television can have both positive and negative impacts on early childhood development, including cognitive development. The role of parents in this case is very necessary, one of which can guide and supervise shows that are worth watching for their children according to age limits